Testing of Thesis Management Application Using STLC Framework and Automation Tools in Physics Study Program UPN “Veteran” Jatim - Mohamad Irwan Afandi; Abdul Rezha Efrat Najaf; Dewangga Nanda Arjuna (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Thesis administration at the higher education level, such as in the Physics Study Program, still faces challenges due to the absence of an integrated system. To address this issue, a web-based Thesis Management Application was developed to support five main user roles: Students, Lecturers, Thesis Coordinators, Program Coordinators, and Administrators. The system offers a comprehensive set of features including authentication, pre-proposal submission, advisor scheduling, seminar and exam management, publication submission, oral examinations, and final graduation requirements. This study focuses on the Quality Assurance (QA) process using the Scrum methodology and Software Testing Life Cycle (STLC) framework over six sprints conducted within three months. The process began with the mapping of 225 functional requirements on the Front-End and 206 on the Back-End, which were then translated into 1240 test cases derived from various usage scenarios, authorization validations, and interaction flow explorations. Non-functional testing was also conducted at the end of the sixth sprint, covering aspects such as portability, usability, performance, availability, and security. The results show that all system requirements were successfully met, indicating that the application is feasible for supporting a structured thesis administration process.